Nursing education: The continued problem of class, race and gender stereotyping - Rodney, Patricia (Women and Development Unit, UWI, 1993)
This paper examines nursing education as a part of the subordinating apparatus in which the devalued domestic role assigned to women mediates the terms on which nurses participate in the medical profession. It argues that nursing education cannot be separated from the wider range of social institutions that form the governing apparatus of society
Keywords: Nursing education